(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The article highlights the problems of psychological preparation of teachers and shows the changes in the socio-cultural context leading to changes in the educational environment. The article presents a psychological analysis of the nature of pedagogical activity and educates through the teaching process and shows the leading role of communication in pedagogical activity. This analysis creates a basis for determining the main areas of psychological knowledge necessary for a teacher education: general psychology, youth psychology and developmental psychology, social psychology, pedagogical psychology. The article examines the main concepts of psychological training, includes theoretical and practice-oriented teachers, and defines promising directions for the development of psychological training in pedagogical education